Epidemiology of Congenital Rubella Syndrome (CRS) in India, 2016-18, based on data from sentinel surveillance. - Manoj Murhekar; Sanjay Verma; Kuldeep Singh; Ashish Bavdekar; Naveen Benakappa; Sridhar Santhanam; Gajanan Sapkal; Rajlakshmi Viswanathan; Mini P Singh; Vijaya Lakshmi Nag; Sadanand Naik; Munivenkatappa Ashok; et al. (Public Library of Science (PLoS), 2020)
BACKGROUND:Government of India is committed to eliminate measles and control rubella/congenital rubella syndrome (CRS) by 2020. In 2016, CRS surveillance was established in five sentinel sites. We analyzed surveillance data to describe the epidemiology of CRS in India. METHODOLOGY/PRINCIPAL FINDINGS:We used case definitions adapted from the WHO-recommended standards for CRS surveillance. Suspected patients underwent complete clinical examination including cardiovascular system, ophthalmic examination and assessment for hearing impairment. Sera were tested for presence of IgM and IgG antibodies against rubella. Of the 645 suspected CRS patients enrolled during two years, 137 (21.2%) were classified as laboratory confirmed CRS and 8 (1.2%) as congenital rubella infection. The median age of laboratory confirmed CRS infants was 3 months. Common clinical features among laboratory confirmed CRS patients included structural heart defects in 108 (78.8%), one or more eye signs (cataract, glaucoma, pigmentary retinopathy) in 82 (59.9%) and hearing impairment in 51. (38.6%) Thirty-three (24.1%) laboratory confirmed CRS patients died over a period of 2 years. Surveillance met the quality indicators in terms of adequacy of investigation, adequacy of sample collection for serological diagnosis as well as virological confirmation. CONCLUSIONS/SIGNIFICANCE:About one fifth suspected CRS patients were laboratory confirmed, indicating significance of rubella as a persistent public health problem in India. Continued surveillance will generate data to monitor the progress made by the rubella control program in the country.